Synergistic Effects of Dexamethasone and Dexmedetomidine in Extending the Effects of Pectoral I and Pectoral II Blocks for Postoperative Analgesia Following Total Mastectomy with Lymph Node Dissection - Chitneni, Ahish (Clin Pract, 2021)
Regional anesthesia is an important aspect of the overall anesthetic plan for patients. It has the potential to offer superior benefits compared to opioid-based treatment and is an important component of Enhanced Recovery after Surgery (ERAS) protocols. The use of the pectoral type I (PECS I) and pectoral type II blocks (PECS II) has been shown to reduce postoperative pain and opioid consumption in patients undergoing complete mastectomy and breast surgery. We describe the use of dexamethasone and dexmedetomidine to prolong the analgesic effects of these regional blocks in a patient undergoing total mastectomy with lymph node dissection.